Tenascin-C Facilitates Microglial Polarization via TLR4/MyD88/NF-κB Pathway Following Subarachnoid Hemorrhage - Hu ZQ; Ma R; Sun JQ; Peng M; Yuan J; Lai N; Liu J; Xia D (Journal of Inflammation Research)
Zheng-Qing Hu,1,* Ruijie Ma,1,* Jia-Qing Sun,2,* Min Peng,1 Jinlong Yuan,1 Niansheng Lai,1 Jiaqiang Liu,1 Dayong Xia1 1The Translational Research Institute for Neurological Disorders of Wannan Medical College, Department of Neurosurgery, the First Affiliated Hospital of Wannan Medical College (Yijishan Hospital of Wannan Medical College), Wuhu, Anhui, 241001, People’s Republic of China; 2Deparment of Neurosurgery, Nanjing DrumTower Hospital Clinical College of Xuzhou Medical University, Nanjing, 210008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dayong Xia, The Translational Research Institute for Neurological Disorders of Wannan Medical College, Department of Neurosurgery, the First Affiliated Hospital of Wannan Medical College (Yijishan Hospital of Wannan Medical College), Wuhu, Anhui, 241001, People’s Republic of China, Tel +86 13855309791, Email xiady1981@163.comPurpose: This study primarily aims to elucidate the underlying mechanism of Tenascin-C in neuroinflammation and microglia polarization in a mouse model of subarachnoid hemorrhage (SAH).Methods: The subarachnoid hemorrhage model was constructed by injecting blood into the anterior chiasmatic cistern and stimulating primary microglia with hemoglobin in vitro. Then, Imatinib mesylate was used to inhibit Tenascin-C. Through neurological function scoring, brain edema, primary cell extraction, immunofluorescence staining, CCK8, Tunel staining, Elisa, Western blot and other methods, the potential mechanism of Tenascin-C induced microglia cell polarization was explored.Results: The results of this study observed that the expression of Tenascin-C was up-regulated after subarachnoid hemorrhage. Inhibiting the increase of Tenascin-C by imatinib could significantly ameliorate neuroinflammation, neuronal apoptosis, blood brain barrier disruption and brain edema. When the level of Tenascin-C decreased, the numbers of TLR4 positive, MyD88 positive and NF-κB positive microglial cells decreased accordingly. Moreover, after subarachnoid hemorrhage, the number of microglial cells positive for M1-type markers increased significantly. After imatinib inhibited Tenascin-C, the number of M1-type microglial cells decreased and the number of M2-type microglial cells increased significantly.Conclusion: In summary, the elevated level of Tenascin-C after subarachnoid hemorrhage induces the activation of microglia, releasing a large number of inflammatory factors and aggravating early brain injury.Keywords: SAH, microglia, Tenascin-C, polarization